IMPROVING SPEAKING SKILLS IN DEBATE LEARNING USING THE SPONTANEOUS GROUP DISCUSSION (SGD) METHOD OF CLASS X SCIENCE 4 STUDENTS OF SMAN 7 WAJO - Nurul Masita; Ihramsari Akidah; Nurfathana Mazhud (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to improve student learning outcomes in debate learning and can improve students' speaking skills. This type of research is Classroom Action Research (PTK). Several stages carried out in this research include the planning stage, implementation stage, observation stage, and reflection stage. The data and data sources in this research are process data and learning outcomes of class X Science 4 students at SMAN 7 Wajo, totaling 35 people. This research was carried out in three activities, namely pre-cycle, cycle I and cycle II. The data collection techniques used are student observation sheets, student learning outcomes tests and documentation. Data from research analysis uses descriptive and qualitative analysis. The results of research using the spontaneous group discussion method to improve students' speaking skills in debate learning were declared successful. In pre-cycle activities the average student score was 55 and 3 people achieved the KKTP score or 8%. In cycle I the average student score was 69 and 21 people achieved KKTP or 60%. The average score of students in cycle II increased by 85 and reached a KKTP of 33 people or 94%. Based on the results of the research and discussion above, it can be concluded that the spontaneous group discussion method can improve speaking skills in debate learning for class X Science 4 students at SMAN 7 Wajo. Research data conducted during the pre-cycle stage to cycle II showed different results. Namely, each cycle shows an increase in students' speaking skills.